Tales for Yoga: Who has Stolen the Sun? - Therese Dufour (Bharat Om Kids, 2020)
A collection centred on the well-being of the child through the discovery of yoga and gaining control over his emotions Through the words of the tale, yoga invites the child to imitate the characters, their actions and emotions, thanks to the postures that flow naturally in a sequence. This Inuit tale and its postures, full of determination and firmness, give the child the real feeling of well-being as he develops his self-confidence. So the child learns how to conquer his fears from Donoma who
Keywords: Sports Stories -- Sports Stories